2006
DOI: 10.1677/jme.1.02008
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor downregulates vascular endothelial growth factor (VEGF) expression and inhibits VEGF–VEGF receptor 2 binding in diabetic retinopathy

Abstract: It has been shown that the balance between vascular endothelial growth factor (VEGF), a major angiogenic stimulator, and pigment epithelium-derived factor (PEDF), a potent angiogenic inhibitor, is critical for the regulation of vascular permeability and angiogenesis. However, the regulation of the balance is largely unclear. The present study demonstrated that there is a reciprocal interaction between VEGF and PEDF in the retina. PEDF significantly decreased VEGF expression in both retinal capillary endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(158 citation statements)
references
References 49 publications
5
152
1
Order By: Relevance
“…Clinical trials in patients with diabetic macular edema have shown beneficial effects of anti-VEGF agents in reducing retinal vascular permeability as assessed by fluorescein angiography and decreasing macular edema as shown by optical coherence tomography (Avery et al, 2006;Haritoglou et al, 2006;Jorge et al, 2006;Starita et al, 2007). Recent data indicate that intravitreal injections of PEDF can also reduce vascular hyper-permeability in diabetic rats by a process associated with decreased levels of a variety of inflammatory mediators, including VEGF, VEGFR-2, MCP-1, TNF-α and ICAM-1 (Zhang et al, 2006a(Zhang et al, , 2006b). Studies of the mechanisms by which VEGF induces the vascular permeability increase indicate that multiple pathways are involved.…”
Section: Vegf and Vascularmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials in patients with diabetic macular edema have shown beneficial effects of anti-VEGF agents in reducing retinal vascular permeability as assessed by fluorescein angiography and decreasing macular edema as shown by optical coherence tomography (Avery et al, 2006;Haritoglou et al, 2006;Jorge et al, 2006;Starita et al, 2007). Recent data indicate that intravitreal injections of PEDF can also reduce vascular hyper-permeability in diabetic rats by a process associated with decreased levels of a variety of inflammatory mediators, including VEGF, VEGFR-2, MCP-1, TNF-α and ICAM-1 (Zhang et al, 2006a(Zhang et al, , 2006b). Studies of the mechanisms by which VEGF induces the vascular permeability increase indicate that multiple pathways are involved.…”
Section: Vegf and Vascularmentioning
confidence: 99%
“…Evidence from cell culture and in vivo models of neovascularization provides support that PEDF may be an endogenous negative regulator of VEGF expression and also may interfere with VEGF binding to VEGF receptor 2 (Zhang et al, 2006b). In retinal endothelial cells, VEGF downregulated PEDF (Zhang et al, 2006b).…”
Section: Vegf To Pedf Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…To enable this environment, we strategized an early intervention with the non-inhibitory member of the serine protease inhibitor (SERPIN), pigment epithelium-derived factor (PEDF) by considering its anti-inflammatory, anti-oxidant and inhibitory properties on the VEGF-NADPH oxidase pathway among others followed by another exposure to the potent mitogen epidermal growth factor (EGF). 8,9 As a first step toward such a combined therapeutic approach, we investigated the properties of each of these peptides separately on a rodent model of ischemia-reperfusion (I/R) injury. This model exhibits a biphasic course of BBB permeability changes over time and the NTF treatment was initiated and confined to the initial phase of the altered BBB permeability.…”
Section: Introductionmentioning
confidence: 99%
“…To initiate retinal angiogenesis, the delicate balance between proangiogenic and antiangiogenic factors is likely to be shifted, such that mitogenic factors are enhanced and/or inhibitory factors are decreased. In the retina of a diabetic rodent, the antiangiogenic factor, pigment epithelium-derived factor mRNA, and protein expression are reduced and upregulate the angiogenic factor (VEGF) [97][98][99]. The increased levels of MMP-2 and -9 are often found in angiogenesis [100,101].…”
Section: Mmps and Angiogenesismentioning
confidence: 99%